PEMANFAATAN FLASH SEBAGAI APLIKASI PRESENTASI YANGDINAMIS: USE OF FLASH AS A DYNAMIC PRESENTATION APPLICATION - Alex De Kweldju (JISTECH: Journal of Information Science and Technology, 2015)
The application presentation was widely used by most people, such as PowerPoint, offer manyfeatures to make presentation creation become pretty and handy. But then, all the features will restrainuser to prepare a presentation because user can’t use other than those features. Adobe Flash is anapplication with main purpose to create animation in movie or interactive format. By using AdobeFlash features, such as TimeLine and Action Script, we can create dynamic presentation. Not onlyunlimited animations, user can transform the presentation to be interactive presentation, web page, etc.This study used Adobe Flash to create a simple presentation in order to reveal its’ strength andweakness compared to a presentation was created by PowerPoint.